Assistance in Making Spin Game Powerpoint Learning Media for Early Childhood Teachers in Bengkulu City - Sumarsih Sumarsih; Manap Somantri; Asti Putri Kartiwi (Asosiasi Profesi Multimedia Indonesia, 2023)
Knowledge of technology-based learning media and improving the ability of preschool teachers, the ability to make PowerPoint spin game media, as well as the skills to use PowerPoint spin game media in learning. This PPM service aims to improve the competence of ECCE teachers. The method used in this service is to use training methods. The data collection method used in this service is using performance tests and data analysis using percentage techniques. The result obtained in this service is that the service is carried out well. The implementation of this community service can improve the skills of principals and teachers in terms of knowledge and skills in making PowerPoint spin games learning media with good criteria with an average score of 3.2. Meanwhile, if you look at the percentage of success of participants who got very good scores as much as 29%, who got good scores as much as 58.3%, and those who got enough scores as much as 12.5%. So, it was concluded that it can be said that the implementation of training on making power point spin games learning media has been successful.